Development of Scratch-Based Interactive Learning Media to Enhance Fourth-Grade Student’ Conceptual Understanding of Energy Transformation - Zahro, Nur Shoviatul; Ismail, Ali; Sujana, Atep (Papanda Publisher, 2025)
This study aims to develop PORMASI learning media, which stands for Project Scratch Energy Transformation, based on Scratch web to improve fourth-grade students' understanding of energy transformation material and to determine the feasibility of Scratch web-based media in science material in fourth-grade elementary schools, as well as to describe the design of Scratch web-based media development in energy transformation material. The benefits of this research are expected to be one of the learning media solutions that can be used in the classroom for abstract science learning and can help improve students' understanding, especially of energy transformation material. The type of research used is R&D (Research and Development), with the ADDIE development model, which includes the following stages: Analysis, Design, Development, Implementation, and Evaluation. The researcher used the following data collection tools: interview questionnaires, expert validation questionnaires, student response questionnaires, and pretest and posttest essay questions. This study involved 38 students, including 15 boys and 23 girls, for 3 days at a public elementary school in the Solokanjeruk subdistrict. The learning media that had been developed obtained a feasibility rating of 93% from subject matter experts, 93% from media experts, and 97% from language experts, with a student response rate of 77% to this media. Thus, it can be seen that this Scratch web-based media is good and very feasible to use as learning media. This was also proven by the N-Gain results, which obtained a percentage of 58% or were considered quite effective.